Work and Artificial Intelligence: From Algorithmic Transparency Principles to the Right to Knowability - Roberta Covelli (Labour & Law Issues, 2023)
This essay intends to evaluate the configurability of a right to knowledge of digital processes as a corollary of the enunciation of the principles of algorithmic transparency. In fact, IT innovation oscillates between an original cooperative development and its economic exploitation through commercial law instruments such as patents and industrial secrets. Once clarified this trend, the essay intends to investigate the sometimes opposite legal tensions experienced both in matters of privacy, both in administrative law, when decisions are taken through algorithms. Particular attention is paid to the perspectives in the field of labor law, both with respect to the protection of the worker's dignity in the context of the performance of the service, both about the limits of the employer's power of control, and in placement systems and recruiting algorithms, too.